"I believe in faking": The Dilemma of Photographic Realism at the Dawn of Photojournalism. (2nd September 2017) - Tucher, Andie
Abstract: From about 1885 to 1910, the concept of the "fake" was an integral part of an ongoing debate in the USA over how best to represent reality for a mass journalistic audience. Nothing like the nefarious fraud its name might suggest, the term generally referred to the modest embellishment, invention, or correction of details in a story or a photograph to make it seem more vivid and truer to life. In both the newspaper press and the world of photography, some practitioners initially embraced the tactic as both useful for the practitioner and beneficial to the public. After the growing condemnation of the fake in the newspaper world helped to cement the increasing dominance of the professionalized journalist, in photography a vigorous debate carried out in the trade and popular press over the propriety and consequences of manipulating images helped to mark the boundaries of the emerging profession of photojournalism. The debate resonates to this day.